2018
DOI: 10.1097/brs.0000000000002721
|View full text |Cite
|
Sign up to set email alerts
|

Endplate Defect Is Heritable, Associated With Low Back Pain and Triggers Intervertebral Disc Degeneration

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 20 publications
4
42
2
6
Order By: Relevance
“…Kentaro et al demonstrated an association between endplate defect and FJ degeneration in rheumatoid arthritis [24]. Our data add knowledge for the relationship between endplate defect and FJ-originated lower back pain.…”
Section: Discussionsupporting
confidence: 74%
“…Kentaro et al demonstrated an association between endplate defect and FJ degeneration in rheumatoid arthritis [24]. Our data add knowledge for the relationship between endplate defect and FJ-originated lower back pain.…”
Section: Discussionsupporting
confidence: 74%
“…Animal studies have largely overlooked the contribution of genetic background on disc aging phenotypes (Gorth, Shapiro, & Risbud, 2019; Novais et al, 2019; Tessier, Tran, Ottone, & Novais, 2019). This is important since previous studies with twins’ cohorts have reported a strong correlation between familiar aggregation and disc degeneration (Battié, 2009; Munir et al, 2018). Along with the higher grades of disc degeneration seen in SM/J at 6M, they differed the most in terms of gene expression compared to BL6 and LG/J.…”
Section: Discussionmentioning
confidence: 96%
“…A recently published longitudinal twin-cohort study of 438 individuals reported that endplate defects, lumbar disc degeneration and MCs all are independent risk factors for episodes of severe and disabling LBP. Longitudinal analysis showed that MCs followed disc degeneration [8]. Endplate defect has a significant heritability of 55% [8] and clinically, MC are often associated with LBP at all times of the day and nightly pain and morning pain/stiffness are common complaints [9,10].…”
Section: Definition Pathoanatomy and Symptomatologymentioning
confidence: 99%